Pure adhesive film and preparation method thereof
By combining low-Tg and high-Tg saturated polyester resins with epoxy resins, and preparing pure adhesive films using multi-temperature tunnel furnaces, the shortcomings of traditional pure adhesive films in terms of mechanical, aging resistance and storage performance are solved, and high-performance pure adhesive film preparation is achieved.
Patent Information
- Application Number
- CN202411965964.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional pure adhesive films have shortcomings in terms of mechanical properties, aging resistance and storage performance, especially in the problems of poor bonding effect, low peeling and shearing performance, poor aging resistance, harsh storage conditions and short validity periods of materials such as PET, aluminum plates, and steel sheets.
Epoxy modified polyester glue is prepared by combining low-Tg saturated polyester resin and high-Tg saturated polyester resin with epoxy resin, and a pure adhesive film is prepared through a multi-temperature tunnel furnace to improve its peeling, shear and aging resistance, while reducing moisture absorption.
It achieves excellent peeling performance, shearing performance and aging resistance of pure adhesive films, with extremely low moisture absorption rate. It can be placed in a normal temperature and humid environment for 240 hours without layering or bubbles. It also has simple storage conditions and no refrigeration is required, which significantly saves storage costs.
Smart Images

Figure BDA0005218354970000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pure adhesive films, and in particular to a pure adhesive film and a preparation method thereof. Background Art
[0002] Pure adhesive film is a thermosetting semi-cured adhesive film for bonding two interfaces. It is usually used in the field of flexible printed circuit boards (FPC) for the interface bonding of copper foil, steel sheets, aluminum plates, flame-resistant materials (FR4) and polyethylene terephthalate PET or polyimide PI and other materials.
[0003] Traditional pure adhesive films are prepared using epoxy-nitrile and polyacrylate-phenolic system or polyacrylate-epoxy system. However, traditional pure adhesive films generally have the following problems: 1. Limited bonding performance, poor bonding effect on materials such as PET, aluminum plates, steel sheets, and electrophoretic steel sheets, and low peel strength and shear strength; 2. Poor peeling and shearing performance in high and low temperature environments; 3. Poor aging resistance, 85% RH, 150℃ high temperature, -40℃~85℃ high and low temperature impact aging treatment peel strength and shear strength attenuation rate is more than 70%; 4. The general moisture absorption rate is 1.5%-2.5%. After being placed at room temperature and humidity for 1 day, it is easy to delaminate and bubble at 288℃ thermal shock. If the subsequent processing process requires a high temperature process, a high temperature baking process needs to be added; 5. The storage conditions are harsh and the validity period is short. It needs to be stored in a low temperature refrigerator, and the storage cost is high. Summary of the invention
[0004] The invention provides a pure adhesive film and a preparation method thereof, so as to solve the technical problems that the traditional pure adhesive film has poor mechanical properties, aging resistance and storage performance.
[0005] In order to solve the above technical problems, in a first aspect, the present invention provides a pure adhesive film, comprising the following raw material components by mass:
[0006] 15 to 40 parts of low Tg saturated polyester resin;
[0007] 10 to 35 parts of high Tg saturated polyester resin;
[0008] 5 to 20 parts of epoxy resin;
[0009] Curing agent 0.1 to 5 parts;
[0010] Accelerator 0.01 to 1 part;
[0011] 10 to 30 parts of flame retardant;
[0012] 0.1 to 1 part of coupling agent;
[0013] 40 to 110 parts of solvent;
[0014] Among them, the Tg value of the low Tg saturated polyester resin is -10°C to 20°C, the hydroxyl value is 5mgKOH / g to 25KOHmg / g, the acid value is 3mgKOH / g to 30mgKOH / g, and the molecular weight is 10000 to 30000; the Tg value of the high Tg saturated polyester resin is 50°C to 80°C, the hydroxyl value is 3mgKOH / g to 30KOHmg / g, the acid value is 5mgKOH / g to 25mgKOH / g, and the molecular weight is 5000 to 20000.
[0015] In some embodiments, the epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin and glycidyl amine epoxy resin.
[0016] In some embodiments, the curing agent includes any one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate and meta-xylylene diisocyanate.
[0017] In some embodiments, the promoter includes any one or more of 2-methylimidazole, 2-ethylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-methylimidazole urea, 2,4,6-tris(dimethylaminomethyl)phenol, boron trifluoride triethylphosphine, boron trifluoride triisopropylphosphine, trimethylphosphine and triphenylphosphine.
[0018] In some embodiments, the flame retardant includes any one or more of diethyl aluminum phosphite, trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, trioctyl phosphate, melamine, polynitrogen flame retardant melamine phosphate, melamine cyanurate, aluminum hydroxide and magnesium hydroxide.
[0019] In some embodiments, the coupling agent includes any one or more of 3-methacryloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane and isocyanatepropyltrimethoxysilane.
[0020] In some embodiments, the solvent includes any one or more of acetone, butanone, cyclohexanone, toluene, xylene, ethyl acetate and butyl acetate.
[0021] In a second aspect, the present invention further provides a method for preparing a pure adhesive film, comprising the following steps:
[0022] Step 1, weighing the raw material components of the pure adhesive film according to the mass fraction, adding the low Tg saturated polyester resin, the high Tg saturated polyester resin, the epoxy resin, the flame retardant, the coupling agent and the solvent into the adhesive preparation kettle, stirring and dispersing until completely dissolved, and then grinding and dispersing to obtain the adhesive mother solution;
[0023] Step 2, adding an accelerator and a curing agent to the glue mother solution, stirring and dispersing for 20 minutes to 45 minutes, and obtaining an epoxy-modified polyester adhesive;
[0024] Step three, coating, drying, rolling and slitting the epoxy modified polyester adhesive to obtain a finished pure adhesive film.
[0025] In some embodiments, step three includes:
[0026] The epoxy modified polyester adhesive is coated on the surface of the milky white release film at a coating line speed of 10m / min to 20m / min; after baking and drying in a multi-temperature zone tunnel furnace, the transparent release film is attached to the coating layer at a pressing temperature of 50℃ to 60℃; then the film is rolled up and placed in an oven at 50℃ to 60℃ for aging for 10 hours, cooled, and cut to obtain the finished pure adhesive film.
[0027] In some of the embodiments, the multi-temperature zone tunnel furnace includes, according to the tunnel advancing direction, a first baking zone with a temperature of 70°C, a second baking zone with a temperature of 100°C, a third baking zone with a temperature of 130°C, a fourth baking zone with a temperature of 150°C, a fifth baking zone with a temperature of 150°C and a sixth baking zone with a temperature of 100°C.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] The present invention combines low-Tg saturated polyester resin with a Tg value of -10°C to 20°C and high-Tg saturated polyester resin with a Tg value of 50°C to 80°C with epoxy resin to prepare epoxy-modified polyester adhesive, and cooperates with a multi-temperature zone tunnel furnace to prepare a pure adhesive film, so that the pure adhesive film has excellent peeling performance, shear performance and aging resistance, and has extremely low moisture absorption rate. It can be placed in a normal temperature and humidity environment for 240 hours and then subjected to a 288°C thermal shock without stratification or blistering. At the same time, the pure adhesive film prepared by the present invention has simple storage conditions, no refrigeration is required, and the performance is normal after being stored at normal temperature and humidity for 6 months, which greatly saves storage costs; it has extremely low molding temperature and extremely short molding time (110°C-130°C, 60-120S), extremely low curing temperature and extremely short molding time (130°C-150°C, 30-60min), and high production efficiency. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0031] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0032] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0033] In addition, the indefinite articles "a" and "an" before the elements or components of the present invention have no restrictions on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number is obviously intended to be in the singular form.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] Example 1
[0036] A pure adhesive film comprises the following raw material components in parts by mass:
[0037] 36 parts of low Tg saturated polyester resin;
[0038] 13 parts of high Tg saturated polyester resin;
[0039] 5 parts of bisphenol A epoxy resin;
[0040] 2 parts of hexamethylene diisocyanate (HDI);
[0041] 0.01 part of 1-cyanoethyl-2-ethyl-4-methylimidazole;
[0042] 11 parts of aluminum diethylphosphinate;
[0043] Aluminium hydroxide 7 parts;
[0044] 0.3 parts of 3-glycidylpropyltrimethoxysilane;
[0045] Butanone 55 parts;
[0046] Toluene 55 parts;
[0047] Among them, the Tg value of the low Tg saturated polyester resin is -5°C, the hydroxyl value is 6mgKOH / g, the acid value is 3mgKOH / g, and the molecular weight is 25000; the Tg value of the high Tg saturated polyester resin is 56°C, the hydroxyl value is 17mgKOH / g, the acid value is 9mgKOH / g, and the molecular weight is 15000.
[0048] The preparation method of the pure adhesive film comprises the following steps:
[0049] Step 1, weighing the raw material components of the pure adhesive film according to the mass fraction, adding the low Tg saturated polyester resin, the high Tg saturated polyester resin, the epoxy resin, the flame retardant, the coupling agent and the solvent into the adhesive preparation kettle, stirring and dispersing until completely dissolved, and then grinding and dispersing to obtain the adhesive mother solution;
[0050] Step 2, adding an accelerator and a curing agent to the glue mother solution, stirring and dispersing for 30 minutes, and obtaining an epoxy-modified polyester adhesive;
[0051] Step three, coat the epoxy modified polyester adhesive on the surface of the 50um milky white release film, and the coating line speed is 15m / min; then enter the multi-temperature zone tunnel furnace for baking and drying, and then bond the 25um transparent release film to the coating layer, and the pressing temperature is 55°C. The multi-temperature zone tunnel furnace includes a first baking zone with a temperature of 70°C, a second baking zone with a temperature of 100°C, a third baking zone with a temperature of 130°C, a fourth baking zone with a temperature of 150°C, a fifth baking zone with a temperature of 150°C, and a sixth baking zone with a temperature of 100°C according to the forward direction of the tunnel; then roll it up and place it in a 55°C oven for maturation for 10 hours, cool it, and cut it to obtain the finished pure adhesive film.
[0052] Example 2
[0053] A pure adhesive film comprises the following raw material components in parts by mass:
[0054] 40 parts of low Tg saturated polyester resin;
[0055] 10 parts of high Tg saturated polyester resin;
[0056] 6 parts of bisphenol A epoxy resin;
[0057] 1 part of isophorone diisocyanate;
[0058] 0.03 parts of 2,4,6-tris(dimethylaminomethyl)phenol;
[0059] 11 parts of aluminum diethylphosphinate;
[0060] Aluminium hydroxide 7 parts;
[0061] 0.3 parts of 3-glycidylpropyltrimethoxysilane;
[0062] Butanone 55 parts;
[0063] Toluene 55 points;
[0064] Among them, the Tg value of the low Tg saturated polyester resin is 7°C, the hydroxyl value is 9 mgKOH / g, the acid value is 15 mgKOH / g, and the molecular weight is 30,000; the Tg value of the high Tg saturated polyester resin is 63°C, the hydroxyl value is 11 mgKOH / g, the acid value is 10 mgKOH / g, and the molecular weight is 20,000.
[0065] The preparation method of the pure adhesive film is the same as that of Example 1.
[0066] Example 3
[0067] A pure adhesive film comprises the following raw material components in parts by mass:
[0068] 25 parts of low Tg saturated polyester resin;
[0069] 24 parts of high Tg saturated polyester resin;
[0070] 7 parts of bisphenol A epoxy resin;
[0071] 1 part of isophorone diisocyanate;
[0072] 0.02 parts of 1-cyanoethyl-2-phenylimidazole;
[0073] 9 parts of aluminum diethylphosphinate;
[0074] Aluminium hydroxide 9 parts
[0075] 0.5 parts of isocyanate propyltrimethoxysilane;
[0076] Butanone 55 parts;
[0077] Toluene 55 parts;
[0078] Among them, the Tg value of the low Tg saturated polyester resin is 19°C, the hydroxyl value is 8mgKOH / g, the acid value is 18mgKOH / g, and the molecular weight is 15000; the Tg value of the high Tg saturated polyester resin is 65°C, the hydroxyl value is 22mgKOH / g, the acid value is 14mgKOH / g, and the molecular weight is 10000.
[0079] The preparation method of the pure adhesive film is the same as that of Example 1.
[0080] Example 4
[0081] A pure adhesive film comprises the following raw material components in parts by mass:
[0082] 15 parts of low Tg saturated polyester resin;
[0083] 34 parts of high Tg saturated polyester resin;
[0084] 6 parts of bisphenol A epoxy resin;
[0085] 1 part of isophorone diisocyanate;
[0086] 0.05 part of 2,4,6-tris(dimethylaminomethyl)phenol;
[0087] 9 parts of aluminum diethylphosphinate;
[0088] Aluminium hydroxide 9 parts
[0089] 0.5 parts of isocyanate propyltrimethoxysilane;
[0090] Butanone 55 parts;
[0091] Toluene 55 parts;
[0092] Among them, the Tg value of the low Tg saturated polyester resin is -5°C, the hydroxyl value is 6 mgKOH / g, the acid value is 3 mgKOH / g, and the molecular weight is 10,000; the Tg value of the high Tg saturated polyester resin is 56°C, the hydroxyl value is 17 mgKOH / g, the acid value is 9 mgKOH / g, and the molecular weight is 5,000.
[0093] The preparation method of the pure adhesive film is the same as that of Example 1.
[0094] Comparative Example 1
[0095] The epoxy-nitrile pure adhesive film includes the following raw material components by mass:
[0096] 23 parts of carboxyl-terminated nitrile rubber;
[0097] 25 parts of bisphenol A epoxy resin;
[0098] 9 parts of aluminum diethylphosphinate;
[0099] Aluminium hydroxide 9 parts;
[0100] 4 parts of 4,4'-diaminodiphenyl sulfone;
[0101] 0.5 part of dicyandiamide;
[0102] Butanone 55 parts;
[0103] Toluene 55 parts
[0104] The preparation method of the pure adhesive film is the same as that of Example 1.
[0105] Comparative Example 2
[0106] The difference from Example 1 is that a 150° C. oven is used instead of a multi-temperature zone tunnel oven.
[0107] Comparative Example 3
[0108] The difference from Example 1 is that the Tg value of the low Tg saturated polyester resin is 30°C, the hydroxyl value is 30KOHmg / g, the acid value is 50mgKOH / g, and the molecular weight is 50000; the Tg value of the high Tg saturated polyester resin is 100°C, the hydroxyl value is 50KOHmg / g, the acid value is 30mgKOH / g, and the molecular weight is 30000.
[0109] 1. Peel strength test:
[0110] 180° peel strength:
[0111] Reference test standard: GB / T 7122-1996 Determination of peel strength of high-strength adhesives - floating roller method.
[0112] ①Prepare support plate material samples (125*50*2mm).
[0113] ② Prepare a layer of thermosetting adhesive film and use a precision cutter to cut it into 10mm*300mm strips. (Actual test uses 10mm strips)
[0114] ③ Clean the above test board with an appropriate amount of solvent, and prepare to paste the sample after drying.
[0115] ④ According to the actual production plan, hot press the cut PI film strips onto the support plate strips until the thermosetting adhesive is fully cured and cooled.
[0116] The test was carried out using a constant speed tensile testing machine (300 mm / min), and the average value was automatically taken in the interval and the data was recorded.
[0117] 2. Shear strength test:
[0118] Reference test standard: GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material).
[0119] Select the test adhesive material according to the actual adhesive surface material and make a standard shape sample:
[0120] The actual support plate substrate specimen used is: length 100mm±0.25mm, width 25mm±0.25mm, thickness 1.6mm±0.1mm;
[0121] The samples were hot pressed and bonded, with a bonding surface of 12.5 mm ± 0.25 mm. It is recommended to use double-sided hot pressing, pressing both sides of the PI film hot pressing film on the aluminum sheet or hot pressing the aluminum sheet on one side and bonding the other side with a high-strength adhesive.
[0122] Choose a suitable tensile testing machine: the breaking load of the specimen should be between 10% and 80% of the maximum load of the tensile testing machine, and the response time of the testing machine should be short enough to ensure the accuracy of the fracture time determination;
[0123] Clamp the sample on the fixture, and the distance from the clamp to the nearest bonding end is 50mm±1mm. Use the tensile machine to stretch at a rate of 5mm / min and record the curve. The maximum stress during the failure process is the failure load F (N), which is divided by the bonding area A (mm2) to obtain the dynamic shear strength δ (MPa): δ = F / A.
[0124] 3.-40℃~85℃ hot and cold shock aging test:
[0125] Refer to "GB / T 2425.22 Environmental testing Part 2: Test method Test N: Temperature change".
[0126] The samples are placed in an alternating temperature environment of -40℃ ~ 85℃. The conversion time between the two extreme temperatures is within 30 minutes. The samples are kept in each extreme temperature environment for 30 minutes, one cycle is 2 hours, 500 cycles, and a total of 1000 hours before testing.
[0127] 4.85℃, 85%RH aging test:
[0128] Refer to GB / T 2425.3 Environmental testing Part 2: Test method Test Cab: Steady state damp heat test.
[0129] The samples were placed in a constant temperature and humidity chamber with the temperature set at 85±3℃ and the humidity set at 82%-88%RH for 1000 hours, then taken out and placed at room temperature for another 2 hours before testing.
[0130] 5.150℃ high temperature aging test:
[0131] Set the temperature of the sample to 150±5℃, take it out after 1000h, and place it at room temperature for another 2h before testing.
[0132] 6. Water absorption test:
[0133] The sample should be wiped with a clean wet cloth for more than three times, placed in an oven at 105-110℃ for 1h, taken out and placed in a desiccator to cool to room temperature, and weighed immediately after being taken out of the desiccator. Weigh each treated sample separately and record it, accurate to 0.1mg; put the sample into a container filled with distilled water, all edges should be completely immersed in water, and the water temperature should be maintained at 23±1.1℃. After 24+0.5 / -0h, take all the samples out of the water at once, wipe off the surface moisture with a dry cloth and weigh them immediately. The moisture absorbed by the weighing bottle material during the weighing process has been confirmed to have no significant effect on the measurement results. Weight increase % = (weight after immersion - weight before immersion) / weight before immersion x 100.
[0134] Table 1 Performance test results of Examples 1 to 4 and Comparative Example 1
[0135]
[0136] The high-performance pure adhesive film prepared in Examples 1 to 4 uses epoxy-modified polyester adhesive as an adhesive, and has high adhesive strength. The peel strength is greater than 1N / mm and the shear strength is greater than 10MPa at room temperature and humidity. The peel strength is greater than 1N / mm and the shear strength is greater than 7MPa at -30°C and humidity. The peel strength is greater than 1N / mm and the shear strength is greater than 3MPa at -30°C and humidity. The moisture absorption rate is extremely low, and the moisture absorption rate after curing is less than 0.8%. After the product is placed at room temperature and humidity for 240 hours, it undergoes a thermal shock at 288°C without delamination or blistering. It has excellent aging resistance. Properties: Excellent high temperature and high humidity aging performance, the peel strength and shear strength decay rate is less than 20% after 1000h treatment at 85℃ and 85%RH, and the peel strength and shear strength decay rate is less than 50% after 2000h; excellent long-term high temperature aging performance, the peel strength and shear strength decay rate is less than 30% after 1000h continuous baking at 150℃, and the peel strength and shear strength decay rate is less than 60% after 2000h; excellent high and low temperature impact aging performance, the peel strength and shear strength decay rate is less than 15% after 500 cycles of -40-85℃ high temperature and low temperature impact. Comparative Example 1 is an epoxy-nitrile pure adhesive film, and Comparative Document 2 uses a 150℃ oven instead of a multi-temperature tunnel oven. The polyester resin of Comparative Document 3 is different from that of Example 1. Obviously, the peel strength and weather resistance of Comparative Documents 1 to 3 are not as good as those of Examples 1 to 4.
[0137] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0138] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A pure adhesive film, characterized in that: The invention comprises the following raw material components by weight: 15 to 40 parts of low Tg saturated polyester resin; 10 to 35 parts of high Tg saturated polyester resin; Epoxy resin 5 to 20 parts; Curing agent 0.1 to 5 parts; Accelerator 0.01 to 1 part; 10 to 30 parts of flame retardant; 0.1 to 1 part of coupling agent; 40 to 110 parts of solvent; Among them, the Tg value of the low Tg saturated polyester resin is -10°C to 20°C, the hydroxyl value is 5mgKOH / g to 25KOHmg / g, the acid value is 3mgKOH / g to 30mgKOH / g, and the molecular weight is 10000 to 30000; the Tg value of the high Tg saturated polyester resin is 50°C to 80°C, the hydroxyl value is 3mgKOH / g to 30KOHmg / g, the acid value is 5mgKOH / g to 25mgKOH / g, and the molecular weight is 5000 to 20000.
2. The pure adhesive film according to claim 1, characterized in that: The epoxy resin includes any one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin and glycidyl amine epoxy resin.
3. The pure adhesive film according to claim 1, characterized in that: The curing agent includes any one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate and meta-xylylene diisocyanate.
4. The pure adhesive film according to claim 1, characterized in that: The accelerator includes any one or more of 2-methylimidazole, 2-ethylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-methylimidazole urea, 2,4,6-tris(dimethylaminomethyl)phenol, boron trifluoride triethylphosphine, boron trifluoride triisopropylphosphine, trimethylphosphine and triphenylphosphine.
5. The pure adhesive film according to claim 1, characterized in that: The flame retardant includes any one or more of diethyl aluminum phosphinate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, trioctyl phosphate, melamine, polynitrogen flame retardant melamine phosphate, melamine cyanurate, aluminum hydroxide and magnesium hydroxide.
6. The pure adhesive film according to claim 1, characterized in that: The coupling agent includes any one or more of 3-methacryloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane and isocyanatepropyltrimethoxysilane.
7. The pure adhesive film according to claim 1, characterized in that: The solvent includes any one or more of acetone, butanone, cyclohexanone, toluene, xylene, ethyl acetate and butyl acetate.
8. A method for preparing a pure adhesive film according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, weighing the raw material components of the pure adhesive film according to the mass fraction, adding the low Tg saturated polyester resin, the high Tg saturated polyester resin, the epoxy resin, the flame retardant, the coupling agent and the solvent into the adhesive preparation kettle, stirring and dispersing until completely dissolved, and then grinding and dispersing to obtain the adhesive mother solution; Step 2, adding an accelerator and a curing agent to the glue mother solution, stirring and dispersing for 20 minutes to 45 minutes, and obtaining an epoxy-modified polyester adhesive; Step three, coating, drying, rolling and slitting the epoxy modified polyester adhesive to obtain a finished pure adhesive film.
9. The method for preparing a pure adhesive film according to claim 8, characterized in that: The step three comprises: The epoxy modified polyester adhesive is coated on the surface of the milky white release film at a coating line speed of 10m / min to 20m / min; after baking and drying in a multi-temperature zone tunnel furnace, the transparent release film is attached to the coating layer at a pressing temperature of 50℃ to 60℃; then the film is rolled up and placed in an oven at 50℃ to 60℃ for aging for 10 hours, cooled, and cut to obtain the finished pure adhesive film.
10. The method for preparing a pure adhesive film according to claim 9, characterized in that: The multi-temperature zone tunnel furnace includes, according to the tunnel advancing direction, a first baking zone with a temperature of 70°C, a second baking zone with a temperature of 100°C, a third baking zone with a temperature of 130°C, a fourth baking zone with a temperature of 150°C, a fifth baking zone with a temperature of 150°C and a sixth baking zone with a temperature of 100°C.